Expectation gap em auditoria : um estudo sobre a formação, modificação e ênfase de opinião do auditor independente - Camelo, Augusto César Oliveira (2017)
The expectation gap in auditing is caused by the difference in expectations among professionals, stakeholders and society in general. This phenomenon feeds the critic environment against auditors, wears the trust linkage between the latter and the users of accounting information and is seen as harmful for professional well-being. In such context and also with the recent changes incorporated by the Brazilian Accounting Standards to meet the standards proposed by the International Standards on Auditing on the new set of standards named the New Report of the Independent Auditor (NRA), this research was aimed towards the investigation of the expectation gap in the Brazilian context, in special, about the perception of independent auditors and accounting information users about the normative content for formation, modification and emphasis of opinion, limiting itself to the objective excerpts, definitions and requirements of each standard. With this fragmentation, the research construct was originated. Characterized as quantitative, descriptive and survey-oriented, this study aimed to identify the amplitude of the expectation means among the participants of the research, utilizing descriptive and test statistics to assess the difference of perception of each inquired about the proposed construct. In sequence, the questionnaire was applied to the auditors and users by means of the Google Drive Forms platform. The final sample accounted for 114 participants (71 auditors and 43 users). The answers obtained were tabulated and inserted in the SPSS software and after the normality test of data, the research hypotheses were legitimized by means of a Mann-Whitney test (U Test). The results obtained verified the existence of an expectation gap between auditors and users regarding the normative content for the formation and modification of auditor's opinion; though, some questions of the two constructs did not show differences. In relation to the emphasis of opinion, the equality hypothesis between the means of auditors and users was kept, concluding that there was not enough evidence to reject the null hypothesis; thus characterizing that there was no difference in expectations for this construct. In sum, the research identified the existence of the expectation gap between auditors and users for normative content of formation and modification of opinion.